Penyiram Tanaman Bunga (Florikultura) Otomatis dengan sistem IoT Berbasis Arduino - Pane, Rahmadani; Sepriani, Yusmaidar (JURNAL AGROPLASMA, 2024)
Gardening and planting flowers is a fun and relaxing hobby for some people. The obstacle that arises is the availability of maintenance time, especially for watering plants. However, maintaining flower plants for those of us who are busy workers often experience maintenance time constraints. Busy owners cannot pay adequate attention and this results in delays in watering which result in plants not being able to grow and develop properly or dying. On the other hand, excessive watering will cause plants to become susceptible to illness due to excessive/high water levels. This research is aimed at producing a solution in the form of a system that can keep the water content in plant pots balanced using an automatic watering mechanism or based on remote control. Apart from that, it also uses the Blynk application installed on the smartphone to monitor soil moisture values, temperature values and watering notifications. The watering results show the watering categories including a lot, moderate, little and no watering. This research produces a tool that can water rose plants automatically according to temperature and humidity sensors with notifications on smartphones. The result is a prototype automatic plant watering IoT system with Arduino and smartphone control. Based on testing using the black box method, this system is operational and solves research problems. Keywords: plant, IoT, watering, floricuture